Pengaruh Perilaku Religiusitas Terhadap Perilaku Konsumsi Produk Kemasan - Wahyuni, Wahyuni; Hasni, Hasni; Haslindah, Haslindah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2022)
This study aims to determine the behavior of religiosity on the consumption behavior of cosmetic packaging products. The object of this research is the women community in Lili Riawang Village, Bengo District, South Sulawesi, Indonesia. The type of research used is field research using a quantitative approach method. The data collection technique used is descriptive statistical analysis. The results of this study indicate that the behavior of religiosity affects the consumption behavior of cosmetic packaging products in the female community in Lili Riawang Village, Bengo District, South Sulawesi Indonesia. R Square value of 70.3% indicates that the behavioral factor of religiosity is very influential on consumption behavior, while the remaining 29.7% is influenced by other factors.